Analisis Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak - Teuku Radhifan Syauqi (Jurnal Riset AKuntansi dan Bisnis, 2021)
This research aims to test the influence of service, consultation and supervision by the Account Representative on taxpayer compliance The results of regression tests found that partially the service variables, consultation and supervision by the Account Representative have a significant effect on taxpayer compliance, simultaneously service variables, consultation and supervision by the Account Representative have a significant effect on taxpayer compliance. Furthermore, obtained a correlation coefficient (R) value of 0.587 and an Adjusted R Square value of 0.325 indicates that service, consultation and supervision by the Account Representative has an influence on taxpayer compliance of 32.5% and the remaining 67.5% is explained by other factors not included in the study.